Selenium treatment alters the effects of UV radiation on chemical and production parameters in hybrid buckwheat. (2nd January 2018) - Golob, Aleksandra; Stibilj, Vekoslava; Kreft, Ivan; Vogel-Mikuš, Katarina; Gaberščik, Alenka; Germ, Mateja
ABSTRACT: Ambient UV radiation is recognised as an important environmental factor in the regulation of plant growth and development, and selenium (Se) as a beneficial nutrient that can increase plant tolerance to different environmental constraints. The effects on hybrid buckwheat plants of full (+UV) and reduced (−UV) ambient UV radiation without (−Se) and with (+Se) foliar Se treatment (10 mg L −1 sodium selenate) provided the four conditions of Se−UV–, Se–+UV, +Se−UV and +Se+UV. Plant morphological, biochemical and physiological properties were examined, along with leaf elemental composition and content, efficiency of Se enrichment, and production parameters. Leaf anatomical parameters under all conditions were mainly affected by UV radiation, and less so by Se. +Se+UV plants showed a trade-off between primary and secondary metabolism, which resulted in high levels of protective substances (e.g. anthocyanins, UV absorbing compounds), and low levels of photosynthetic pigments. All +UV plants were significantly shorter in comparison to those under the reduced −UV, while biomass production was highest for −Se+UV plants and lowest for +Se+UV plants. +Se plants accumulated ∼20-fold greater Se content compared to −Se plants, and full ambient UV radiation partly reduced this effect. +UV plants showed increased phosphorus content in leaves, independent of Se status, while +Se plants showed increased K content. Si content was increased by Se treatment and decreased by the full UV exposure. Se treatment and the ambient UV radiation, separately have positive effects on growth and production of this hybrid buckwheat, while the combination of the Se treatment and ambient UV resulted in lower yields. However, under these conditions (+Se+UV), the buckwheat plants established good protection against the different environmental constraints that are becoming more and more frequent due to changes to our climate.